Hotel Social Media Content as a Strategy for Developing Tourism in Bali: A Content Analysis of Hotel Indigo Seminyak Beach Bali’s Instagram Social Media Content - Ageng Ratna Sari; Putu Bella Ayu Virdani (Jurnal Indonesia Sosial Sains, 2026)
Bali is one of the most popular tourism destinations in the world. Based on data from Badan Pusat Statistik (BPS), the number of international tourist arrivals to Bali in 2024 reached 6.3 million visitors. This study aims to determine the role of student management in shaping student character at SMPIT Plus Dar El Hijrah. This study used a descriptive qualitative approach with observation, interviews, and documentation methods. Then, through data validity testing and conclusion drawing, the data can be presented US research findings. Students at SMPIT Plus Dar El Hijrah have not yet demonstrated good behavior. This is evident in the many students who violate or refuse to comply with their teachers' instructions. || the importance of discipline for students, this study aims to examine student management in shaping student character at SMPIT Plus El Hijrah. It is hope that the results of this study can contribute to the development of more effective educational strategies in shaping student discipline. The results of this study relate to the formation of student character discipline at SMPIT Plus Dar El Hijrah, Ciseeng District.